Redefining Individual Growth and Development Indicators: Oral Language. (September 2014) - Bradfield, Tracy A.; Besner, Amanda C.; Wackerle-Hollman, Alisha K.; Albano, Anthony D.; Rodriguez, Michael C.; McConnell, Scott R.
Language skills developed during preschool contribute strongly to later reading and academic achievement. Effective preschool assessment and intervention should focus on core components of language development, specifically oral language skills. The Early Language and Literacy Individual Growth and Development Indicators (IGDIs) are a set of measures that have demonstrated utility in language and early literacy assessment, evaluation, and intervention studies. The purpose of this article is to describe two studies conducted to build on the existing oral language IGDI, Picture Naming, to increase utility for instructional decision making, particularly within an early childhood Response to Intervention framework. Study 1 outlines the initial development and piloting of potential measures and Study 2 describes the revision and continued analysis of the most promising measures. Results of Study 1 and Study 2 indicate that Picture Naming has continued utility as a measure of oral language skill development and that one newly developed oral language IGDI, Definitional Vocabulary, has potential utility.